Role of AMP-activated protein kinase in kidney tubular transport, metabolism, and disease. Issue 5 (September 2017) - Rajani, Roshan; Pastor-Soler, Nuria M.; Hallows, Kenneth R.
Abstract : Purpose of review: AMP-activated protein kinase (AMPK) is a metabolic sensor that regulates cellular energy balance, transport, growth, inflammation, and survival functions. This review explores recent work in defining the effects of AMPK on various renal tubular epithelial ion transport proteins as well as its role in kidney injury and repair in normal and disease states. Recent findings: Recently, several groups have uncovered additional functions of AMPK in the regulation of kidney and transport proteins. These new studies have focused on the role of AMPK in the kidney in the setting of various diseases such as diabetes, which include evaluation of the effects of the hyperglycemic state on podocyte and tubular cell function. Other recent studies have investigated how reduced kidney mass, polycystic kidney disease (PKD), and fibrosis affect AMPK activation status. A general theme of several conditions that lead to chronic kidney disease (CKD) is that AMPK activity is abnormally suppressed relative to that in normal kidneys. Thus, the idea that AMPK activation may be a therapeutic strategy to slow down the progression of CKD has emerged. In addition to drugs such as metformin and 5-aminoimidazole-4-carboxamide ribonucleotide that are classically used as AMPK activators, recent studies have identified the therapeutic potential of other compounds that function at least partly as AMPK activators, such as salicylates, statins, berberine, and resveratrol, in preventing the progression of CKD. Summary: AMPK in the kidney plays a unique role at the crossroads of energy metabolism, ion and water transport, inflammation, and stress. Its potential role in modulating recovery from vs. progression of acute and chronic kidney injury has been the topic of recent research findings. The continued study of AMPK in kidney physiology and disease has improved our understanding of these physiological and pathological processes and offers great hope for therapeutic avenues for the increasing population at risk to develop kidney failure.